Expression of neuropeptide Y and its receptors Y1 and Y2 in the rat heart and its supplying autonomic and spinal sensory ganglia in experimentally induced diabetes - Chottová Dvoráková, M; Wiegand, S; Pesta, M; Slavíková, J; Grau, V; Reischig, J; Kuncová, J; Kummer, W (Neuroscience, 2008)
Diabetic cardiomyopathy, involving both cardiomyocytes and the sensory and autonomic cardiac innervation, is a major life-threatening complication in diabetes mellitus. Here, we induced long-term (26-53 weeks) diabetes in rats by streptozotocin injection and analyzed the major cardiac neuropeptide signaling system, neuropeptide Y (NPY) and its receptors Y1R and Y2R. Heart compartments and ganglia supplying sympathetic (stellate ganglion) and spinal sensory fibers (upper thoracic dorsal root ganglia=DRG) were analyzed separately by real-time reverse transcription-polymerase chain reaction (RT-PCR) and immunohistochemistry. Ventricular, but not atrial innervation density by NPY-immunoreactive fibers was diminished, and preproNPY expression was transiently (26 weeks) reduced in left atria, but remained unchanged in sympathetic neurons and was not induced in DRG neurons. In all ganglia and heart compartments, Y1R expression dominated over Y2R, and Y1R-immunoreactivity was observed on cardiomyocytes and neuronal perikarya. Atrial, but not ventricular Y1R expression was up-regulated after 1 year of diabetes. Collectively, these data show that a disturbance of the cardiac NPY-Y1R/Y2R signaling system develops slowly in the course of experimentally induced diabetes and differentially affects atria and ventricles. This is in parallel with the clinically observed imbalances of the cardiac autonomic innervation in diabetic cardiac autonomic neuropathy.
Keywords: Diabetes Mellitus, Experimental; Neuropeptide Y; Streptozocin; Receptors, Neuropeptide Y; regulace genové exprese; experimentální diabetes mellitus; Female; krysa rodu Rattus; spinální ganglia; zvířata; potkani Wistar; časové faktory; neuropeptid Y; ženské pohlaví; ganglion stellatum; Gene Expression Regulation; Rats, Wistar; Stellate Ganglion; Rats; myokard; streptozocin; Animals; receptory neuropeptidu Y; Myocardium; Ganglia, Spinal; Time Factors